2006
DOI: 10.1080/15257770600894196
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Atorvastatin on Extracellular Nucleotide Degradation in Human Endothelial Cells

Abstract: Endothelial degradation of extracellular nucleotides is known to be an important mechanism in regulation of thrombosis, inflammation and immune response. It is possible that this pathway is a target for pleiotropic drugs such as atorvastatin. We studied therefore the effect of atorvastatin on extracellular nucleotide degradation in human endothelial cells. Atorvastatin treatment of human umbilical vein endothelial cells (HUVEC) and human microvascular endothelial cells (HMEC-1) resulted in significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Many of these signaling factors are similar to those found in vascular atherosclerosis and bone formation. Matrix MetalloProteinases (MMP)53, 62, Interleukin 163, Transforming growth factor-beta(TGF-beta)64, purine nucleotides42, 65, RANK66, osteoprotegrin(OPG)66, and TNF alpha67, have all been identified as signaling pathways important in the development of this disease process. Evidence, for the angiotensin converting enzyme pathway expressed and colocalize with LDL in calcified aortic valves also plays a role in future potential medical therapy68.…”
Section: Osteoblast Phenotype Is the Final Common Pathway For Aortic mentioning
confidence: 99%
“…Many of these signaling factors are similar to those found in vascular atherosclerosis and bone formation. Matrix MetalloProteinases (MMP)53, 62, Interleukin 163, Transforming growth factor-beta(TGF-beta)64, purine nucleotides42, 65, RANK66, osteoprotegrin(OPG)66, and TNF alpha67, have all been identified as signaling pathways important in the development of this disease process. Evidence, for the angiotensin converting enzyme pathway expressed and colocalize with LDL in calcified aortic valves also plays a role in future potential medical therapy68.…”
Section: Osteoblast Phenotype Is the Final Common Pathway For Aortic mentioning
confidence: 99%
“…Previous studies demonstrated that statins (3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitors) reduce serum low-density lipoprotein (LDL) cholesterol, which is associated with a significant reduction in cardiovascular events. [1][2][3][4] Statins also have cholesterol-independent pleiotropic effects, such as upregulation of ecto-59-nucleotidase, [5][6][7][8] activation of the phosphatidylinositol 3-kinase-Akt pathway, 9 activation of the ERK 1/2 pathway 10 and upregulation of nitric oxide (NO) synthase. 11,12 These pleiotropic actions may contribute to the cardioprotective effects of statins, such as an improved tolerance against ischemia and reperfusion injury (IR injury).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that statins induce ecto-5Ј-nucletidase activation and increased interstitial adenosine formation in a setting of acute myocardial infarction in rabbits (46). Statin administration increases ATP breakdown and adenosine formation in human umbilical vein endothelial cells and human microvascular endothelial cells (34). The increased interstitial adenosine is an important trigger of K ATP channel opening (46).…”
mentioning
confidence: 99%